RANCANG BANGUN PENGOLAH AIR HUJAN MENJADI AIR MINUM BERBASIS ELEKTROLISIS AIR DENGAN SMART CONTROL SYSTEM BERFILTER UV - Sugiantara, I Putu; Aelin, I Kadek; Raka Agung, I Gusti Agung Putu; Elba Duta Nugraha, I Putu; Rahardjo, Pratolo (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
The water crisis in Bali, especially in Badung Regency, encourages the use of rainwater harvesting technology as a conservative solution. This research develops an electrolysis-based rainwater treatment system with IoT integration and UV filters at SMAN 1 Mengwi. Electrolysis technology separates acid and alkaline ions to produce drinking water from rainwater. pH and TDS sensors to determine the pH and turbidity level of the water in the reservoir. IoT-based smart control system monitors and controls the system online from an Android cellphone. The test results showed that the variation in the capacitance of the adapter (1 ?F–680 ?F) accelerated electrolysis from 90 minutes to 30 minutes, with an output voltage of 310 V –321 V. Statistical tests proved the effect of capacitance on voltage (sig. 0.006) and electrolysis time (sig. 0.000). UV filters have been able to sterilize bacteria up to 0 E. Coli based on laboratory test results. In conclusion, the system works precisely with a 1% RSD in monitoring water quality, while the large capacitance increases the voltage and efficiency of electrolysis. Further research is suggested to explore current variations, diodes, and the development of more adaptive smart control algorithms .